Land structure and level of fragmentation in typical small-marginal agricultural holdings in India - ROY, SNEHA; SINGH, ASHOK KUMAR; BERA, SAMIR KUMAR; BHATTACHARYA, SHRADDHA (The Indian Journal of Agricultural Sciences, 2020)
Farming in the Indian subcontinent is essentially small and marginal. With time, land size is fast declining and farmers are under pressure of generating more and more surplus under extreme resource competition. Land fragmentation has also increased severely in recent times, which might pose a threat to sustainability and food security soon by making agriculture unprofitable. The present study aims to portray the dismal condition of the land structure and level of land fragmentation of 141 small-marginal farming households in one of the most fertile agro-ecological villages of West Bengal in India, Rautari village in Chakdah block situated in Nadia district. Present investigation was conducted through well-structured field studies during 2016–17. The study reveals the existence of very traditional patriarchal land ownership patterns, and lack of women’s inclusion from property ownership rights. Farmlands are extremely fragmented with a high value of Simpson Index. Moreover, farmers with high technical efficiency fragment it even more to accommodate a greater number of crops in one growing season. A positive relation between farm area and production is derived from field data. Based on the prevailing situation, indicated by results, the study designed a comprehensive community and land resources utilization plan for the development of the community in the study area. The proposed comprehensive community and land resources utilization plan is a structured tool for extension services which will strengthen the capacity building programs for small-marginal farmers.